(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Today, the competence approach in the educational process implies the formation and development of practical skills that allow students to act effectively in situations encountered in professional, personal and everyday life, as well as strengthening the practical, applied directions of mathematical education.